2008
DOI: 10.1111/j.1365-2702.2007.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital anomalies: parents’ anxiety and women's concerns before prenatal testing and women's opinions towards the risk factors

Abstract: Prenatal tests, both routine screening and prenatal diagnosis, cause anxiety for parents. Understanding women's concerns and awareness of risk factors are important for providing care and counselling. Relevance to clinical practice. Nurses can provide appropriate information and support at each step in the screening and diagnosis process so that parents' psychological stress is minimised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
2
24
1
3
Order By: Relevance
“…Several studies proved that a higher level of knowledge was associated with a lower level of emotional distress and anxiety. (5) On the contrary, our study revealed that the association between women's Table 1. Distribution of sociodemographic and obstetric characteristics by invasive prenatal diagnosis of Down syndrome Table 2.Distribution of knowledge, perceived risk for invasive procedure of Down syndrome in pregnant women Table 3.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Several studies proved that a higher level of knowledge was associated with a lower level of emotional distress and anxiety. (5) On the contrary, our study revealed that the association between women's Table 1. Distribution of sociodemographic and obstetric characteristics by invasive prenatal diagnosis of Down syndrome Table 2.Distribution of knowledge, perceived risk for invasive procedure of Down syndrome in pregnant women Table 3.…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies claim that pregnant women with inadequate information and less knowledge about prenatal testing had higher anxiety scores than women with more knowledge of prenatal diagnosis. (5) On the contrary, a study by Rowe et al (6) claims that anxiety levels of pregnant women who were well informed were not significantly different from those who were poorly informed. (6) In addition, psychological responses are also influenced by women's perceived risk of having an abnormal baby.…”
Section: Introductionmentioning
confidence: 81%
“…The absence of distress was also found which is a psychological benefit that sharply contrasts with women's experiences of invasive testing, which carries a risk of miscarriage. 21 Regarding the disadvantages of NIPD, very few issues were raised by participants and concerns such as the burden of 'unnecessary' decision-making for pregnancies that may spontaneously abort 22 were outweighed by the potential benefits of NIPD. One concern raised by a number of participants was around social sexing.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our hypothesis, men reported to a higher degree than women that their partners had a much higher influence on their decision. This may reflect the power that is attributed to women in pregnancyrelated decisions, as it is often believed they should have the final word in whatever choice concerns their body (Browner & Preloran, 1999), especially considering the risk of miscarriage associated with the procedure, along with the female's physical discomfort that is often mentioned by couples as an amniocentesis-related concern (Cederholm et al, 1999;Sahin & Gungor, 2008). However, it remains to be known whether men and women perceive this apparent unbalance.…”
Section: Decision-making Process Regarding Amniocentesismentioning
confidence: 99%
“…On the other hand, men's presence is also associated with higher levels of decisional conflict (regarding IDTs) and anxiety in women, prior to the first appointment. As a coping strategy, some women may ask for partner's support, while those who have more confidence in their decision might not need their partners to be present (Humphreys et al, 2003;Sahin & Gungor, 2008).…”
Section: Men's Attendance Of Genetic Counseling and The Decision-makimentioning
confidence: 99%